Mesoporous Silica-Based Catalysts for Biodiesel Production: A Review - Is Fatimah; Ganjar Fadillah; Suresh Sagadevan; Won-Chun Oh; Keshav Lalit Ameta (ChemEngineering, 2023)
High demand for energy consumption forced the exploration of renewable energy resources, and in this context, biodiesel has received intensive attention. The process of biodiesel production itself needs to be optimized in order to make it an eco-friendly and high-performance energy resource. Within this scheme, development of low-cost and reusable heterogeneous catalysts has received much attention. Mesoporous silica materials with the characteristics of having a high surface area and being modifiable, tunable, and chemical/thermally stable have emerged as potential solid support of powerful catalysts in biodiesel production. This review highlights the latest updates on mesoporous silica modifications including acidic, basic, enzyme, and bifunctional catalysts derived from varied functionalization. In addition, the future outlook for progression is also discussed in detail.